Protocol for a Phase Two, Parallel Three-Armed Non-inferiority Randomized Controlled Trial of Acceptance and Commitment Therapy (ACT-Adjust) Comparing Face-to-Face and Video Conferencing Delivery to Individuals With Traumatic Brain Injury Experiencing Psychological Distress - Whiting, Diane L.; Simpson, Grahame K.; Deane, Frank P.; Chuah, Sarah L.; Maitz, Michelle; Weaver, Jerre (Frontiers in Psychology, 2021)
Background: People with traumatic brain injury (TBI) face a range of mental health challenges during the adjustment process post-injury, but access to treatment can be difficult, particularly for those who live in regional and remote regions. eHealth provides the potential to improve access to evidence-based psychological therapy for people with a severe TBI. The aim of the current study is to assess the efficacy of a psychological intervention delivered via video consulting to reduce psychological distress in people with TBI. Methods: This paper outlines the protocol for a multi-centre, three-arm, parallel, non-inferiority randomized controlled trial (RCT) of an evidence-based manualized psychological intervention, ACT-Adjust. ACT-Adjust provides nine sessions for adults with a moderate to severe TBI experiencing clinical levels of psychological distress. Fifty-six participants referred from Brain Injury Rehabilitation Units across New South Wales (NSW) and the NSW icare scheme will be randomly allocated to three conditions; (1) video consulting (VC), (2) face-to-face (FtF) and, (3) a waitlist control (WL). Discussion: This is the first RCT to evaluate the efficacy of a psychological therapy (ACT-Adjust) delivered via video consulting for individuals with a moderate to severe TBI. Trial registration: Registered with the Australian New Zealand Clinical Trials Registry (ANZCTRN2619001602112) www.anzctr.org.au on 21 November 2019. Dated 30th September 2019; Protocol version 1.0